-1 = z/3 - 7
Emily's Work:
-1 = z/3 - 7
-1(3)=z/3(3)-7
-3 = z - 7
-3 -7 = z - 7
z = -10
Right away without having to start at the beginning, I see that she has made a mistake at the 4th-5th line of work.
Instead of adding 7 to both sides, she subtracts it and still leaves it in and doesn't fully finish the equation, as it would really be z-7 = -10
In order to solve it, follow these steps:
Rewrite the initial equation as follows:
x/3 - 7 = -1
Multiply both sides by 3
x/3(3)-7(3)=-1(3)
x - 21 = -3
Add 21 to both sides
x = 18